2022
DOI: 10.1213/ane.0000000000006272
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the FRAIL Scale and Postoperative Complications in Older Surgical Patients: A Systematic Review and Meta-Analysis

Abstract: BACKGROUND: Several frailty screening tools have been shown to predict mortality and complications after surgery. However, these tools were developed for in-person evaluation and cannot be used during virtual assessments before surgery. The FRAIL (fatigue, resistance, ambulation, illness, and loss of weight) scale is a brief assessment that can potentially be conducted virtually or self-administered, but its association with postoperative outcomes in older surgical patients is unknown. The objective of this sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…However, the assessment instrument used in this study is the FRAIL scale, which has the advantages of briefness, accuracy, and ease of administration. Our ndings support that the FRAIL scale can predict adverse events in the postoperative period, which is consistent with the results of previous studies [19,22,23] .…”
Section: Discussionsupporting
confidence: 93%
“…However, the assessment instrument used in this study is the FRAIL scale, which has the advantages of briefness, accuracy, and ease of administration. Our ndings support that the FRAIL scale can predict adverse events in the postoperative period, which is consistent with the results of previous studies [19,22,23] .…”
Section: Discussionsupporting
confidence: 93%
“…The original cognitive battery included Montreal Cognitive Assessment (MOCA) (Spanish version and telehealth or blind version as necessary), 24,25 Hopkins Verbal Learning Test Revised (HVLTR), 26 copy gure from Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), 27 Geriatric Depression Scale (GDS) (available in multiple languages including English, Spanish and Portuguese), 28 and the FRAIL scale. 29 The modi ed cognitive battery only included the MOCA, GDS, and the FRAIL scale. MK, a neuropsychologist at the University of Miami, developed the protocol for virtual cognitive test visits according to her clinical practice.…”
Section: Study Proceduresmentioning
confidence: 99%
“…They also reported that the presence of frailty was a predictor of postoperative neurological, renal, vascular, and respiratory system complications in patients who went through both cardiac and non-cardiac surgical procedures. 32 Even though the mechanism remains unclear, the surge in neuroinflammatory mediators following both cardiac and non-cardiac surgical interventions has been reported to be a strong predictor of POCD. We have seen that most of the literature in this review article supported this argument (n=8).…”
Section: Dovepressmentioning
confidence: 99%